4x

^{2}+6x=04x^{2}+6x=0

Tutors, please sign in to answer this question.

Aliquippa, PA

4x^{2} + 6x = 0

x(4x + 6) = 0

which means

4x + 6 = 0 ⇒4x = -6 or **x = -3/2**

Stephanie M.

NYU Trained Singer for Voice Lessons

New York, NY

5.0
(2 ratings)

Hanh P.

Published Cancer Researcher Specializing in Sciences, Psych, Writing

New York, NY

5.0
(2 ratings)

Scott L.

Test prep done right: Don't try to survive your test, CRUSH it!

New York, NY

4.9
(1220 ratings)

- Math 8582
- Math Help 4842
- Word Problem 4720
- Algebra 4547
- Math Word Problem 3843
- Algebra 1 3735
- Algebra 2 3150
- Algebra Word Problem 2300
- Calculus 2016
- Physics 1993